The collaboration of the private sector in the North American Free Trade Agreement renegotiation. Analysis of the Mexican automotive industry - Nava-Aguirre, Karla Maria (Universidad Autónoma de Tamaulipas, 2021)
The renegotiation of the North American Free Trade Agreement between Mexico, the United States and Canada began as a protectionist measure of United States in 2017. The importance of this agreement involved the active participation of the Mexican private sector through the “Side Room” a mechanism that functions as a consulting body for negotiation of international agreements. The automotive industry was a sensitive issue due to the integration level of the supply chains and their impact for the North American region. The objective of this research was to analyze the collaboration of the private sector automotive industry in the public consultation processes of the Mexican government for the definition of Mexico’s trade policy during the North American Free Trade Agreement renegotiation period. This is a qualitative research with a descriptive-exploratory scope. Nine semi-structured interviews were carried out with representatives of the Mexican government, experts, or active members of the “Side Room”. The “Side Room” consulting mechanism allowed the Mexican Government to align most of the private sector interests to the country’s trade policy. Although the agreements reached regarding the rules of origin, and the increment on the regional value content of auto parts may require greater participation from the North American macro region, they allow new opportunities for the development of the domestic industry in Mexico. The experience of the Mexican private sector, the negotiation skills and interaction through the “Side Room” and above all, the intense lobbying in the with the private sector, legislators, and governors before and during renegotiation, had a positive impact for the Mexican government in order to satisfactorily conclude the negotiations. The transparency of the public-private consulting process consolidated alliances inside and outside Mexico, albeit with complex challenges.